Dietary effect of carotenoids from golden snail eggs on colour enhancement in Koi fish Cyprinus carpio Linnaeus 1758 - Sukarman; A. Sofyan; B. Nur; S. Cindelaras; S. Murniasih; S. Rohmy; T. Kadarini; Nurhidayat; M. Zamroni; M. F. Chaniago; R. Ginanjar (Brazilian Journal of Biology)
Abstract This study aims to evaluate the growth and pigmentation of koi fish (Cyprinus carpio) fed with carotenoids from golden snail eggs (GSE). Fish were fed a control diet (0 ppm), supplemented with 75 ppm, 150 ppm and 225 ppm of carotenoid from GSE for 60 days. Growth was checked at 10-day intervals, while skin colour was assessed using a colourimeter to measure the chroma (C*), lightness (L*) and hue (H*) of the red zone of the skin. Total carotenoid (TC) concentrations were also analysed in the muscle, fin and skin tissues. The inclusion of carotenoid from GSE did not significantly affect growth, but a notable enhancement in chroma and hue (P < 0.05) was observed at the 225 ppm inclusion level. Furthermore, the 225 ppm diet significantly increased TC concentration in the skin (P < 0.05), without influencing levels in the muscle or fin. These findings suggest that supplementation with 225 ppm carotenoid from GSE effectively enhances koi skin pigmentation without compromising growth.